Mignon's afterlives crossing cultures from Goethe to the twenty-first century - Cave, Terence (Oxford : Oxford University Press, 2011)
Terence Cave traces the afterlives of Mignon, an apparently minor character in Goethe's novel Wilhelm Meisters Lehrjahre through the European cultures of the 19th and 20th centuries. The enigmatic and fascinating Mignon reappears in wide range of different works, mainly narrative fiction but also poetry, song opera, and film.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Goethe, Johann Wolfgang von, -- 1749-1832 -- Characters -- Mignon; Mignon (Fictitious character); European literature -- 19th century -- History and criticism; European literature -- 20th century -- History and criticism